First molecular detection of Mycoplasma agassizii in captive tortoises in Portugal - Louro, Manuel; Patrício, Rui; Pereira, André; Valença, Andreia; Alves, Margarida (Frontiers in Veterinary Science, 2025)
IntroductionMycoplasma agassizii is a well-recognized etiologic agent of upper respiratory tract disease in tortoises. Although frequently reported in both captive and wild populations across Europe, its occurrence in Portugal had not been previously documented. This study aimed to investigate the presence of M. agassizii in apparently healthy captive tortoises in mainland Portugal and to evaluate potential host- and management-related factors associated with infection.MethodsOral swabs were collected from 84 tortoises of 13 species across 3 geographic regions. DNA extraction success and sample integrity were confirmed by partial amplification of the tortoise mitochondrial 12S rRNA gene in 92.9% of cases (78/84), which were then screened for M. agassizii using a species-specific PCR targeting the 16S rRNA gene.Results and discussionThe pathogen DNA was detected in 66.7% (52/78) of individuals. Phylogenetic analysis confirmed species identification, with all sequences forming a strongly supported monophyletic cluster together with M. agassizii reference sequences. A significant association was observed between tortoise genus and M. agassizii infection (p = 0.021), with Chelonoidis exhibiting a significantly lower infection frequency than Testudo (p = 0.029). No statistically significant associations were observed regarding geographic region, housing origin, or group size. These results reveal a high frequency of M. agassizii infection in apparently healthy captive tortoises in Portugal, emphasizing its potential for silent transmission in group or mixed-species settings. Our findings support the inclusion of this pathogen in the differential diagnosis of respiratory disease in tortoises, even when clinical signs are absent and underscore the need for routine molecular surveillance and strengthened biosecurity practices to mitigate transmission risks and foster chelonian conservation efforts.